The Effect of Prolonged Exposure to Extremely Low Frequency Electromagnetic Fields on the β2 Adrenergic System Activity in the Small Intestine of Male Rats - Esmaeil Khoshnam; Marzyeh Jaafari; Amin Bahaoddini; Maryam Owjfard (Fasa University of Medical Sciences, 2016)
Background & Objective: Electromagnetic waves with the frequencies of 0-300 Hz and the intensity of 0.1-100 millitesla can affect several cellular activities. Therefore, the purpose of this study is to investigate the effect of prolonged exposure to extremely low frequency electromagnetic fields (ELF) on the adrenergic system in the small intestine. Materials & Methods: 21 adult male rats were divided into three groups. The first group was experimental group which exposed to ELF (50Hz, 1mT) for 75 days in powered on solenoid. The second group was sham group which was kept in similar conditions as the first group but in powered off solenoid. The third group or the control group was kept in animal house condition. The isolated strips of the colon were inserted into organ bath and were linked to power lab A to D system force transducer and their mechanical activity were recorded in response to different doses of Isoproterenol (10-4 M and10-5 M). The data were analyzed using one-way ANOVA test. Result: The results showed a significant increase (p≤0.05) of ileum basal contractions in experimental group compared to control and sham groups. While the relaxation changes of ileum in response to the different doses of isoproterenol (β2 adrenergic receptors agonist) in the experimental group compared to the sham and control groups was not statistically significant. Conclusion: It can be concluded that prolonged exposure to extremely low frequency electromagnetic fields may not affect β2 -adrenergic receptors activity.